Semantik dan Pragmatik terhadap Variasi Redaksi Verbal Teks: Menyingkap Makna Kontekstual dalam Studi Matan Hadis - Lestari, Wiwin Dwi (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2021)
The study of hadith matn (content) is equally important as the study of sanad (chain of transmission), particularly in exploring linguistic phenomena to uncover deeper meanings. This article is based on the work of Fatihunnada and Nailil Huda, who examine patterns of verb shifts within the Prophet’s hadith texts, using semantic and pragmatic approaches. The focus is on the variations in past (madhi), present/future (mudhari’), and imperative (amr) verb forms across different narrations, and how these variations reflect specific contextual meanings. The study finds that although certain textual shifts might appear to deviate from formal Arabic grammar, they highlight the hadith's rhetorical eloquence and communicative effectiveness. Through morphosyntactic, semantic, and pragmatic analyses, it is demonstrated that such variations do not undermine the legal values of the hadith but instead enrich their interpretation according to context. For instance, verb changes indicate levels of intensity, reciprocity, or divine intervention, especially concerning eschatological events. The article also offers critical notes on the methodology employed by Fatihunnada and Huda, particularly regarding the limited clarification of their theoretical framework. In conclusion, this study emphasizes the importance of linguistic analysis, especially through semantic and pragmatic methods, for a comprehensive understanding of hadith texts. Such an approach ensures that the authentic meanings of the hadith are preserved and can be appropriately understood and practiced by the Muslim community.